Virtual Reconstruction of Lost Cultural Heritage – The Case of the Historical Church of Pammegist Taxiarch Archangel Michael in Medieval City of Corfu. A holistic Interdisciplinary approach, in Challenging Times enhancing Sustainable Urban Development - Polymeri, Evi (Technical Annals, 2023)
The present work is about the application of digital record of Lost Cultural Heritage monument in Corfu island - the case of the Church of Pammegistos Taxiarch Michael situated in the heart of the oldest medieval district of ‘Campiello’ in the Old Town of Corfu, built at the 14th century. Today the building has been demolished and a homonymous square has been created in its place. The "Taxiarch square" is a free space formed randomly, violently and as a remnant after the bombings of the 2nd World War. Considering an essential step in understanding and conserving the values of the memory of the glorious past, creating a as close as possible digital record of the most important monument in the area for the future, providing a means to communicating the knowledge and value of the tangible monument to the society. Our effort aims to efficiently open new orisons to the locals, in upgrading the living standard, while through culture and dialogue we might provide the necessary transformative dimension that ensures the sustainability of development processes. In our Challenging Times the data coming to light from in-situ research, the archives, bibliography etc., applied to the following modelling features the role of 3D virtual reconstruction of the important monument of cultural heritage in Corfu Old Town – a UNESCO World Heritage Site in Greece acquires even greater importance, supporting archaeological and architecture research and art history, used as well as a vehicle for the cultural and evocative involvement of the people.